The sustainability of indigenous lands in Amapá state - Campos, Alcinéia Miranda; Nascimento, Francisco Gean Freitas do; Cunha, Helenilza Ferreira Albuquerque (Sustainability in Debate, 2022)
We herein assess population growth in indigenous lands (ILs) Wajãpi, Uaçá, Galibi and Juminã in Amapá State-Brazil, which has influenced deforestation increase. We assumed the hypothesis of no association between demographic density and deforestation because population density in these areas is low. We used population growth, deaths, and deforestation data by considering a historical series (2002-2018). Demographic data have shown that Uaçá and Wajãpi ILs recorded the highest population growth. The highest demographic density was observed for Galibi ILs and the lowest one for Wajãpi ILs. The highest deforestation was observed for Uaçá ILs and the lowest one for Juminã ILs. Therefore, indigenous lands in Amapá State have an essential role in forest conservation.